Temperature dependent structural and vibrational properties of hydroxyapatite: A theoretical and experimental study - Kebiroglu, M. Hanifi; Orek, Cahit; Bulut, Niyazi; Kaygili, Omer; Keser, Serhat; Ates, Tankut (Elsevier Sci Ltd, 2017)
We describe the temperature dependence of the vibrational, rotational and translational partition functions of the activated complex of hydroxyapatite (HAp). Computed data show that the vibrational modes have a larger contribution towards the partition function of HAp compared to the rotational and translational contributions. Xray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy have been applied for HAp in the temperature range from 730 degrees C to 1030 degrees C at steps of 100 degrees C. Temperature dependent density functional theory (DFT), B3LYP, and Ground State Hartree-Fock (HF) with 6-311G basis set calculations were also applied to HAp to calculate FTIR spectra, HOMO, and LUMO energies, and density of states (DOS), and the results have been compared to experimental findings. The present results underline that experimental measurements and theoretical calculations of unit cell parameters, and the intensities of most of the FTIR data for HAp are nearly independent on temperature.
Keywords: Hydroxyapatite; DFT and HF calculations; FTIR; Partition function